2020
DOI: 10.1039/d0ra08619c
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium swelling of thermo-responsive copolymer microgels

Abstract: A model is developed for equilibrium swelling of thermo-responsive copolymer gels and is applied to predict the effect of molar fraction of comonomers on the volume phase transition temperature of macroscopic gels and microgels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…60 Copyright 2020, American Chemical Society contraction of hydrogel also exemplifies hydrophobicity when heated. 177 Grunlan et al suggested a double network (DN) PNIPAAm hydrogel system to enhance thermosensitivity compared to a single network (SN) hydrogel without increasing the VPTT. 66 DN hydrogels were also prepared as micropillar arrays to increase cell-release efficiency when the temperature underwent VPTT (Figure 13(E)).…”
Section: Thermal Actuationmentioning
confidence: 99%
“…60 Copyright 2020, American Chemical Society contraction of hydrogel also exemplifies hydrophobicity when heated. 177 Grunlan et al suggested a double network (DN) PNIPAAm hydrogel system to enhance thermosensitivity compared to a single network (SN) hydrogel without increasing the VPTT. 66 DN hydrogels were also prepared as micropillar arrays to increase cell-release efficiency when the temperature underwent VPTT (Figure 13(E)).…”
Section: Thermal Actuationmentioning
confidence: 99%
“…[171] Drozdov et al demonstrated the versatility of this production method by comparing PNIPAmbased microgels co-polymerized with tert-butylacrylamide (tBA), AA, hydroxyethylmethacrylate (HEMA), triethyleneglycol methacrylate (TREGMA), acrylamide, and N,N'-dimethylacrylamide. [22] The team showed that the chemical composition governs the size and swelling ratio of the resultant microparticles, resulting in microgels with the hydrodynamic diameter ranging from tens of nm to >1 µm and swelling ratios up to 5-fold. The simplicity and scalability of this process, together with its innate pairing with thermo-responsive monomers, makes precipitation polymerization one of the most popular procedures for microgel synthesis.…”
Section: Precipitation Polymerizationmentioning
confidence: 99%
“…Microgels are fabricated in a wide range of sizes, spanning across tens of nanometers to tens of micrometers, depending upon the chemical composition and molar ratio of the monomers, and the synthetic method. [22][23][24] The swelling ratio, defined as the relative weight fraction of water within the microparticle, [25] can also be adjusted either during preparation, [26][27][28] or in real-time by leveraging environmentally-responsive monomers and additives. [29][30][31][32][33] Reversible swelling behavior is arguably the most often exploited feature of microgel coatings, as it provides a means to control both morphological and physicochemical properties of the coated surface.…”
mentioning
confidence: 99%
“…The hydrodynamic radius R h of the microgel particles was measured by dynamic light scattering in the interval of temperatures between 25 and 55 °C. The equilibrium degree of swelling Q()T is determined using the equation 63 1+Q()T1+Q()T*goodbreak=Rh()TRh()T*30.25em with T*=25°normalC and Q()T*=3.…”
Section: Fitting Of Experimental Datamentioning
confidence: 99%